FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PENYANDANG AUTISM SPECTRUM DISORDER (ASD) DI SEKOLAH KHUSUS WILAYAH JABODETABEK TAHUN 2023 - Citra Ramadhanty (2023)
The prevalence of people with Autism Spectrum Disorder (ASD) in Indonesia is estimated to increase by 500 people annually. Various nutritional status-related problems are present in ASD sufferers. This study aims to determine the relationship between mothers' education level, parenting style, knowledge of balanced nutrition, and parental income with the nutritional status of people with ASD in special schools in the JABODETABEK area. This research is an observational study with a cross-sectional design involving 114 respondents obtained using the quota sampling technique. Univariate and bivariate analyses using the Spearman Rank test were conducted. The results showed that people with ASD had an average good nutritional status (0.81). Bivariate analysis showed a significantly strong relationship between parenting style and the nutritional status of people with ASD (p=0.007, r=0.250), indicating a positive correlation between parenting style and social status. However, no relationship was found between mothers' education level (p=0.949), knowledge of balanced nutrition (p=0.728), and parents' income (0.976) with the nutritional status of ASD sufferers. It is concluded that parenting style has a significant relationship with the nutritional status of people with ASD. It is recommended that parents improve parenting for people with ASD, especially regarding food selection and feeding rotation cycles.